Multinational Financial Management / Fourth Edition - Shapiro Alan C (Addison-Wesley Publishing Company, 1992)
Preface, Environment of International Financial Management, Introduction: Multinational Enterprise and Multinational Financial Management, The Foreign Exchange Market, Currency Futures and Options Markets, The Determination of Exchange Rates, The International Monetary System, The Balance of Payments and International Economic Linkages, Parity Conditions in International Finance and Currency Forecasting, Foreign Exchange Risk Management, Measuring Accounting Exposure, Managing Accounting Exposure, Measuring Accounting Exposure, Managing Economic Exposure, Multinational Working Capital Management, Financial Foreign Trade, Current Asset Management, Foreign Investment Analysis, International Portfolio Investment, Financing Foreign Operations, Special Financing Vehicles, Designing a Global Financing Strategy, International Banking, Index.
Preface, Environment of International Financial Management, Introduction: Multinational Enterprise and Multinational Financial Management, The Foreign Exchange Market, Currency Futures and Options Markets, The Determination of Exchange Rates, The International Monetary System, The Balance of Payments and International Economic Linkages, Parity Conditions in International Finance and Currency Forecasting, Foreign Exchange Risk Management, Measuring Accounting Exposure, Managing Accounting Exposure, Measuring Accounting Exposure, Managing Economic Exposure, Multinational Working Capital Management, Financial Foreign Trade, Current Asset Management, Foreign Investment Analysis, International Portfolio Investment, Financing Foreign Operations, Special Financing Vehicles, Designing a Global Financing Strategy, International Banking, Index.